Portrait of an Ottoman Armenian Artist of Constantinople - Vazken Khatchig Davidian (Études Arméniennes Contemporaines, 2014)
This essay contends with two interconnected issues: firstly, considers the problematic manner in which biography has been used as method in art historiography; and, secondly, offers a reflection arising from the unsatisfactory treatment of the Ottoman art historical past by canonical art historiographies of which biography is a central building block. The critical rereading of both text and image components of the biography of Constantinople artist Simon Hagopian (1857-1921), published in the 1912 edition of Teotig’s (1873-1928) Everyone’s Almanac (Ամէնուն Տարեցոյցը) is aimed at exposing these inadequacies. While the reliability of biography is tested against contemporary material, the artist’s output and experience are discussed with their wider social context and intellectual environment in mind. Furthermore, the painter is presented as the ‘normal exceptional’ subaltern artist who, in the name of all excluded and misrepresented artists, speaks back to constructed and artificial canonical narratives that silence his voice.